Mission impossible: A reading of the after-death of the heroine. Issue 2 (15th March 2017) - Boncori, Ilaria
ABSTRACT: Based on two articles written by Heather Höpfl [2003, "Becoming A Virile Member: Women and the Military Body." Body and Society 9 (4): 13–30; 2010, "The Death of the Heroine." Management & Organizational History 5: 395–407] this paper investigates the depiction of the heroine in action movies through a close reading of the blockbuster movie series Mission: Impossible comprising of five films released between 1996 and 2015. This article explores the relationship between gender stereotypes, traditionally male professional environments and the changing role of the heroine. We consider three aspects of the heroine: her body, her relationship to the hero and her role in the movie's representational economy. We conclude by suggesting that the role of female characters has considerably evolved in popular culture over the past decades, which is evidenced in this movie series by a shift from the traditional subordinate supporter female role to a more equal view of a co-hero/ine. Our paper builds on Heather's work and offers an empirical contribution to the use of visual data in organization studies.